The Iran-Iraq War : New international perspectives. - Ashton, Nigel (Cold War history series., 2012)
This volume offers a wide-ranging examination of the Iran-Iraq War (1980-88), featuring fresh regional and international perspectives derived from recently available new archival material. Three decades ago Iran and Iraq became embroiled in a devastating eight-year war which served to re-define the international relations of the Gulf region. The Iran-Iraq War stands as an anomaly in the Cold War era; it was the only significant conflict in which the interests of the United States and Soviet Union unwittingly aligned, with both superpowers ultimately supporting the Iraqi regime. <I.